The effect of packaging materials on the physicochemical stability of ground roasted coffee - Sri Agustini; Mimi Kurnia Yusya (Current Research on Bioscences and Biotechnology, 2020)
This research was intended to evaluate the effect of packaging materials on the stability of physicochemical properties of ground roasted coffee during storage at room temperature (28±2°C) and relative humidity (RH) 80% for 12 months. The packaging material used was aluminium-laminated polyethylene (ALP) and polyethylene terephthalate (PET). The physicochemical characteristics observed were non-volatile fractions consisted of moisture, crude fibre, ashes, the alkalinity of ashes, pH, microbiological load, total phenolic and caffeine contents. The results showed that the moisture content of ground coffee was below 5.0 % for both packaging materials. The overall adsorbed moisture of ground coffee was significantly different (p<0.05) for both packaging materials, whereby the moisture content of ground roasted coffee packaged in PET was 4.15% while of those packaged in ALP was 3.38% by the end of 12 months storage. There was no significant decrease in the ashes, the alkalinity of ashes, crude fibre, pH, total phenolic and caffeine contents for both packaging materials. The total plate count (TPC) decreased from an initial of 1.2 x 103 to be 1.7 x 102 CFU/g. Both packed ground roasted coffees were microbiologically safe as it had TPC less than 105 CFU/g after 12 months storage. The results indicated that ALP and PET packaging can preserve the quality and stability of the ground coffee during storage.